2020
DOI: 10.1021/acs.jpclett.0c00370
|View full text |Cite
|
Sign up to set email alerts
|

Electron–Electron Dipolar Interaction Poses a Challenge to the Radical Pair Mechanism of Magnetoreception

Abstract: A visual magnetic sense in migratory birds has been hypothesized to rely on a radical pair reaction in the protein cryptochrome. In this model, magnetic sensitivity originates from coherent spin dynamics, as the radicals couple to magnetic nuclei via hyperfine interactions. Prior studies have often neglected the electron−electron dipolar (EED) coupling from this hypothesis. We show that EED interactions suppress the anisotropic response to the geomagnetic field by the radical pair mechanism in cryptochrome and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 55 publications
2
77
1
Order By: Relevance
“…Since the present study was not designed to unravel the mechanisms underlying the observed effects, our results pose little preference for any of the interaction models proposed in the literature [Binhi, 2002; Hore and Mouritsen, 2016; Babcock and Kattnig, 2020]. In spite of this, our results do suggest the presence of an amplitude window, so they are prone to be explained by models that predict ranges of enhanced effectiveness.…”
Section: Resultscontrasting
confidence: 59%
“…Since the present study was not designed to unravel the mechanisms underlying the observed effects, our results pose little preference for any of the interaction models proposed in the literature [Binhi, 2002; Hore and Mouritsen, 2016; Babcock and Kattnig, 2020]. In spite of this, our results do suggest the presence of an amplitude window, so they are prone to be explained by models that predict ranges of enhanced effectiveness.…”
Section: Resultscontrasting
confidence: 59%
“…FADH- is then re-oxidized independently of light to FADox. During this step, a second radical pair is formed ( Figure 2 ), possibly with O 2 ∙ (see, e.g., Ritz et al, 2009 ; Müller and Ahmad, 2011 ), but the true partner of FADH ∙ and details of this process are still under debate (see, e.g., Hogben et al, 2009 ; Lee et al, 2014 ; Worster et al, 2016 ; Kattnig, 2017 ; Nielsen et al, 2017 ; Player and Hore, 2019 ; Babcock and Kattnig, 2020 ; Procopio and Ritz, 2020 ).…”
Section: Cryptochrome Forming Radical Pairsmentioning
confidence: 99%
“…63,116 We note that several have been recently proposed, including a light-driven mechanism mirroring photolyase chemistry, and alternative radical pair components through protein-protein or small molecule interactions, 4,14,51 potentially including a third radical. 117 The recent advent of a tractable genetic model in the monarch butterfly should greatly expand our understanding of magenetoreception over the next several years.…”
Section: Protein-protein Interactions and Beyondmentioning
confidence: 99%